Present and Future Flood Hazard in the Lower Columbia River Estuary: Changing Flood Hazards in the Portland‐Vancouver Metropolitan Area. Issue 7 (30th June 2020) - Helaire, Lumas T.; Talke, Stefan A.; Jay, David A.; Chang, Heejun
Abstract: Over the next century, model projections suggest that river run‑off in the Pacific Northwest will increase during the winter season and that sea‐level rise (SLR) may exceed a meter. To investigate the resulting changes in flood hazard, we numerically model the February 1996 and January 1923 floods (the largest and third‐largest Willamette River floods since 1900) under present and potential future run‐off and sea level scenarios. First, we reproduce the actual February 1996 flood to within a root‐mean‐square error of 0.05 m ( N = 7) for peak water levels. Next, we run scenarios in which three SLR scenarios (0, 0.6, and 1.5 m) are combined with two river run‐off scenarios (0% and 10% run‐off increase). Then the slightly larger 1923 flood scenario is run, but with modern (higher than historical) Columbia River flow. The results indicate that a 10% increase in river run‐off increased the1996 flood magnitude by 0.78 m, while 1923 flow increases flood magnitude by 0.82 m. Overall, the type and magnitude of future flood hazards vary with reach. The Portland/Vancouver Metropolitan area is most sensitive to changes in run‐off, with a smaller change of 0.2–0.26 m per meter of SLR. By contrast, coastal regions are quite sensitive to amplified sea level and exhibit nonlinear responses based on changes to river slope and tides. Between the fluvial region and the estuary, a region of compound flood hazard exists that is sensitive to changes in river discharge, sea level, tides, and storm surge. Plain Language Summary: By 2100, scientists predict that Pacific Northwest winter floods will increase in intensity, and ocean sea levels may rise over a meter. To help us understand how climate change (temperature, precipitation, and sea level) may alter peak water levels in a tidal river (specifically in Portland/Vancouver Harbor at the Columbia/Willamette junction) during major floods, we use computers to model major historical and possible future flood events, focusing Willamette River floods in 1923 and 1996, the largest and third‐largest floods since European settlement. The 1996 flood is chosen because its management is characteristic of the present reservoir system. Its unregulated peak would likely have been as large as any historical flood. Results show that the flood hazard away from the coast is most sensitive to changes in river discharge. The sea level rise (SLR) sensitivity is approximately 0.2–0.26 m/m of coastal SLR. By contrast, coastal regions are most sensitive to sea level and storm surge and exhibit complex changes in peak water level due to the changes in the water surface profile and tidal magnitude. Between the lower estuary and tidal river, there is a zone where flood hazard is sensitive to all factors studied (sea level, discharge, tides, and storm surge). Key Points: Sea level rise produces an increase in the 25‐year flood that decreases landward to 20–26% of its coastal value in the Portland/Vancouver Metropolitan area Climate‐induced increases in river flow dominate changes to hazard in the Metropolitan area. River effects become less towards the coast The transition zone between fluvial and coastal flooding, where tides, surge, and flow are all important, shifts landward as sea level rises